Increased level of IL-8 in amniotic fluid in early second trimester linked with preterm pregnancies. - Nikoloska, Katerina; Malahova Gjoreska, Iva; Kjaev, Ivo; Petlichkovski, Aleksandar (ID Design DOOEL Skopje, 2020)
Cytokines (IL-1, IL-6, IL-8, TNF- alfa) are of crucial importance during pregnancy; they are produced by the placenta in the amniotic fluid and they are elevated in case of intrauterine inflammation. The аim of the study was to prove the ratio between the increased IL-8 in the amniotic fluid in the beginning of the second trimester (16-22 g.w.) and premature birth (< 36.6 g.w.). Material and methods: This was a prospective study that included 150 pregnant patients that had clinical indication for amniocentesis (advanced mother’s age, abnormal test of PRISCA I, suspicious anomalies of the fetus, virus infection or mother’s wish). They all gave a signed consent on being informed about the aims of the study, and following the protocol, they were analyzed and examined i.e. all patients underwent ultrasound examination, vaginal cervicometry. Five ml. of amniotic fluid during the process of amniocentesis was taken for the purpose of the study. All patients were followed until they gave birth, and the exact week of gestation was noted and compered with the IL-8 level. Results: All 150 patients were in the period of 16th-22nd gestational weeks. Twenty of the total of 150 patients had preterm delivery. A total of 139 patients conceived naturally and 9 patients underwent in vitro fertilisation (IVF) and embryo transfer (ET). In those with IVF and ET, 3 had preterm birth. 80% of patients that had preterm birth had increased IL- 8 levels. Median cervical length in those who gave birth at term was 32.1 mm and in those who gave preterm birth was 30.7mm. Conclusion: The study has confirmed the reason for examining cytokines as a method of discovering asymptomatic changes in patients who would give a premature birth.
Keywords: preterm birth; amniotic fluid; IL-8; amniocentesis; infection